PENGARUH DERAJAT KEGANASAN TUMOR TERHADAP POLA GAMBARAN EEG PADA PENDERITA TUMOR OTAK PRIMER DI SUMATERA SELATAN - Yunni Diansari,* Sri Handayani,* Achmad Junaidi,* Aspitriani,** Irsan Saleh,*** Wilasari Novantina* (NEURONA, 2020)
INTRODUCTION BRAIN TUMOR IS ONE OF THE MAJOR MALIGNANCIES WITH HIGH MORBIDITY AND MORTALITY TREATMENT OPTIONS AND PROGNOSIS IN PATIENTS WITH PRIMARY BRAIN TUMORS BASED ON THE TYPE AND DEGREE OF MALIGNANCY DEFINITIVE DIAGNOSIS AND DEGREE OF MALIGNANCY IN PATIENTS WITH PRIMARY BRAIN TUMORS OBTAINED FROM HISTOPATHOLOGICAL FEATURES BUT UNFORTUNATELY HISTOPATHOLOGICAL FEATURES ARE NOT ALWAYS AVAILABLE IN ALL PRIMARY BRAIN TUMOR SUFFERERS ELECTRENEFALOGRAPHY EEG EXAMINATION IS A NONINVASIVE EXAMINATION THAT CAN RECORD BIOLOGICAL ACTIVITY AND NEURON CHANGES IN BRAIN CELLS BRAIN TUMOR ITSELF IS AN ABNORMAL MASS IN THE BRAIN TISSUE THAT INTERFERES WITH THE ELECTRICAL AND BIOLOGICAL ACTIVITY OF NORMAL CELLS IN THE BRAIN